Seizure (Henry Christie, ,, 2011)
The new Detective Chief Inspector Henry Christie novel - Newly promoted Detective Superintendent Henry Christie could do without dealing with Felix Deakin, a convicted drug dealer serving a heavy prison sentence, who suddenly volunteers some new evidence that could be crucial in an upcoming murder trial. But things go horribly wrong when Deaken escapes from custody and kidnaps a disgraced ex-cop's some to use as a bargaining chip...

Hidden Witness (Henry Christie, ,, 2011)
The new Detective Superintendent Henry Christie novel - When Detective Superintendent Henry Christie takes on the case of a brutal murder of a seemingly innocent old man, the investigation brings him into touch with old friend and FBI agent Karl Donaldson, who is trying to track down a hit man believed to have entered the UK illegally. It's obvious the two cases are connected, but it soon becomes clear there's more to the old man's murder than simple underworld retribution . . .

Facing Justice (Henry Christie, ,, 2012)
The thrilling new Detective Superintendent Henry Christie novel - When DS Henry Christie sets off on a short winter break with his old friend FBI agent Karl Donaldson, he expects a pleasant hike through the countryside followed by an overnight stop in a picturesque village. But the hike turns into a fight for survival in the worst snowstorm for thirty years. And things only get worse when they stumble, exhausted and injured, into the village pub, only to find themselves in the middle of a blood-soaked stand-off between gangsters with deadly scores to settle . . .

Fighting for the Dead (Henry Christie, ,, 2012)
An apparently straightforward case turns into something far more sinister for Detective Superintendent Henry Christie Detective Superintendent Henry Christie is in the middle of a case involving the horrific murder of a teenage girl when he is called in to investigate the drowning of Jennifer Sunderland, wife of local businessman Harry Sunderland. Henry's curiosity is soon aroused when things don't add up – and when a gun is pointed at his head by a masked man. As Henry starts to dig a simple case of drowning turns into a complex web of deceit, theft, murder and a criminal conspiracy stretching all the way from the UK to Eastern Europe.

Instinct (Henry Christie, ,, 2012)
The thrilling new Detective Superintendent Henry Christie novel - Grieving after a huge personal tragedy, Detective Superintendent Henry Christie is trying to pull his life back together and thinking seriously about retirement – after all, he's got the time in and he'd have a good life and decent pension. But all thoughts of a peaceful dotage are shattered when the phone rings in the early hours, and he is called out to investigate the brutal rape and murder of a teenage girl . . .

Backlash (Henry Christie, ,, 2013)
Transferred from CID to uniform duties, Inspector Henry Christie is back at the sharp end of policing and he's not happy about it -- especially when a brutal murder, apparently the work of a serial killer, takes place on his patch . . .

Bad Tidings (Henry Christie, ,, 2013)
The search for a Christmastime serial killer leads Det. Supt. Henry Christie into the crossfire of warring Lancashire crime families. Lancashire's Chief Constable lures Detective Superintendent Henry Christie away from his much-needed Christmas vacation with the possibility of catching a serial killer. Though he has a new fiancé to celebrate with and an ailing mother to care for, Henry can't refuse the chance to bring a murderer to book. In his thirty years with the Lancashire constabulary, Henry's never dealt with a case like this. Multiple victims disappeared on Christmas Eve, only to turn up gruesomely murdered on New Year's Day. But as he follows the leads to the likely next target-who happens to be the mentally deranged son of a Lancashire crime family-Henry finds himself stepping into a blood-soaked turf war.

Big City Jacks (Henry Christie, ,, 2013)
When the brutally murdered body of a Manchester drug dealer is found dumped just inside the Lancashire border, it turns out that the dead man had been a CID informant working for a small nucleus of corrupt detectives. Then a high-profile trial of a Manchester gangster collapses in disarray, amid accusations of police misconduct.Thrust into the investigation of the drug dealer's death is DCI Henry Christie, recently returned to work after a period of suspension. Hoping for a gentle re-entry into the job, Christie is instead plunged headlong into a complex murder investigation which has far-reaching consequences for the police service...

Critical Threat (Henry Christie, ,, 2013)
DCI Henry Christie, taken off an anonymous murder case and transferred into a dead-end desk job, leaps at the chance to investigate the brutal killing of an ex-cop turned sleazy private eye. At first Christie thinks he will have no trouble identifying the killer, but as he investigates, he stumbles into a plot by Muslim extremists and finds himself plunged into the world of international terrorism. Christie faces his toughest challenge yet as he tries to head off one of the world's most ruthless assassins who has never yet been caught - and who has never yet missed a target.

Dead Heat (Henry Christie, ,, 2013)
Detective Inspector Henry Christie has been suspended from duty. He's spending quality time with his family, and is enjoying being reconciled with wife Kate, but at heart he's bored - and itching to get back into the fray. So when the attractive and wealthy mother of one of his daughter's horse-riding friends asks him to investigate the bizarre mutilation of some of the family's bloodstock, Christie agrees - against his better judgement. He soon finds himself running down dead ends as he discovers that John Lloyd Wickson, Charlotte's father and local multi-millionaire, has enemies in high places. As Henry starts to ask some probing questions he finds himself caught up in a web of corruption and intrigue much wider and more complex than anything he had envisaged . . .

Psycho Alley (Henry Christie, ,, 2013)
A series of increasingly violent assaults is shrouding the happy-go-lucky resort of Blackpool in a veil of terror. It seems only a matter of time before one of these brutal attacks leads to the ultimate crime - murder. The police response, coordinated by an increasingly harassed DCI Henry Christie seems to be getting nowhere fast and the public are growing restless. Then, with the gruesome discovery of a young girl's body, and the abduction of another, Henry finds himself heading a high-profile, nationally scrutinised investigation which stretches his reputation and credibility to breaking point as he finds himself pitted against a devious killer from his past, and, of course, his own inner demons.

Substantial Threat (Henry Christie, ,, 2013)
Crime fiction has just got much, much too real for comfort...

Crunch Time (Henry Christie, ,, 2014)
A DCI Henry Christie Mystery. Willing to do almost anything to escape his desk job, DCI Henry Christie leaps at the chance to go working undercover again. His task, to ingratiate himself with one Ryan Ingram, one of London's top criminals, who has relocated to the north of England. But the last thing Henry needs in this dangerous situation is the appearance of a man bearing a fatal grudge that will jeopardize not only himself, but also his family...

Judgement Call (Henry Christie, ,, 2014)
In this 1980's-set prequel to the popular Henry Christie mysteries, the rookie Lancashire cop is out to prove himself in ways that nearly get him killed. It's 1982, and twenty-three-year-old Henry Christie is determined to make detective in record time. His brief transfer to the Blackburn Criminal Investigation Department ended in disaster. Now he's back in uniform, patrolling the quiet streets of Rossendale Valley, and dreaming up a way to make it back to the CID. He needs to make his mark. And he's about to learn how dangerous ambition can be. Disobeying orders at the scene of a bank robbery gets Henry shot at, and a burglar escapes on his watch. His impetuous actions put him-and his fellow officers-in harm's way. But when a fellow constable is shot down, Henry hunts down her killers with a new sense of resolve in this gritty procedural from the author of Bad Tidings.

Low Profile (Henry Christie, ,, 2014)
A gripping police procedural featuring Detective Chief Superintendent Henry Christie Responding to a desperate phone call, Henry Christie stumbles across a gangland-style execution in progress – and only just escapes with his own life. One of the murder victims is a successful local jeweller, but the motive for his brutal killing remains unclear. Meanwhile, ex-cop Steve Flynn is unwittingly sucked into a deadly game of kidnap, torture and murder. Then, when a dangerous figure from his past emerges, Flynn finds himself slap-bang in the middle of a bloodsoaked race between rival factions for a fortune worth millions. As Henry pieces the evidence together, he starts to unravel links that ultimately pit himself and Flynn against cold-blooded killers who will stop at nothing to achieve their aims – including murdering a cop and his reluctant sidekick.

Screen of Deceit (Henry Christie, ,, 2014)
A DCI Henry Christie novel Fourteen-year-old Mark Carter is plunged into a world of crime following his sister's drug overdose. He agrees to become an informer for DCI Christie in order to avenge Beth's death and redeem himself. But if it all goes wrong, Mark stands to lose everything including his life. Mark's obsession for revenge leads him to a dangerous mixture of teenage street gangs, brutal murder, drug turf wars and betrayal.

Edge (Henry Christie, ,, 2015)
The latest gripping police procedural featuring Detective Chief Superintendent Henry Christie When Charlie Wilder is released from prison he's desperate to resume his life of crime. But when he discovers he's been betrayed by his closest friends, Charlie's rage turns to cold-blooded murder and an orgy of violence ensues ... As a gruesome turn of fate spins Henry Christie unwillingly into a collision course with Charlie, he finds himself pitted against one of the most brutal and dangerous individuals he has encountered in over thirty years as a cop. Fleeing for his life through an unforgiving, harsh, man-made landscape, Henry has to draw on reserves of strength he never knew he had as he discovers there is only one way to beat Charlie Wilder and that is to deliver justice in the only way he understands – by meeting him head-on and taking him right to the very edge ...

The Nothing Job (Henry Christie, ,, 2015)
Reluctantly agreeing to track down three dangerous criminals, DCI Henry Christie's philosophy is that anything that keeps him at the cutting edge of coppering can't be all bad. But then he's asked to close down an investigation into a fatal police shooting, and he uncovers a number of worrying connections. Henry charges headlong into a terrifying conspiracy and finds himself much closer to the cutting edge than even he would have wanted'.

Unforgiving: A Henry Christie thriller (Henry Christie, ,, 2015)
The latest compelling police procedural featuring Detective Chief Superintendent Henry Christie. On the verge of retirement, Henry Christie is loath to leave any unsolved cases to his successor, particularly ones in which he has a personal stake. But when a cop and a suspected murderer are killed in separate but related incidents, Henry's professional judgement is called into question, and it looks as though he will have no choice but to leave the force under a cloud. But he's determined to keep searching for a killer and when the daughter of the new village bobby is abducted, Henry uncovers terrible secrets: secrets that will bring him face to face with a dangerous predator – and the very real possibility that he will become the next victim.

Bad blood: a Henry Christie thriller (Henry Christie, ,, 2017)
As former Detective Superintendent Henry Christie settles into a new life running The Tawny Owl pub with his fiancee Alison, their rural idyll is disrupted by a violent intruder. After Henry foils a kidnap attempt on Alison's daughter, it becomes clear that he and his family have become the targets of a ruthless professinal killer. But who... and why?